Strategy Use in Learning From Multiple Texts: An Investigation of the Integrative Framework of Learning From Multiple Texts - List, Alexandra; Alexander, Patricia A. (Frontiers in Education, 2020)
This study examined undergraduates’ strategy use when learning about a complex and controversial topic (i.e., mass incarceration in the United States) based on information presented across multiple texts. Guided by the Integrated Framework of Learning from Multiple Texts, this study directed students to engage in one of three types of strategy use while learning from multiple texts. In particular, students were asked to identify relevant and important information in texts (i.e., intratextual processing), to form relations or connections across texts (i.e., intertextual processing), or to identify easy or difficult to understand information in texts (i.e., metacognitive processing). In addition to receiving task instructions directing them to engage in these modes of processing, students were also provided with a highlighting tool to scaffold their strategy use (e.g., by allowing important and relevant information to be marked in green, in the intratextual processing condition). This highlighting tool also enabled researchers to collect log data of students’ manifest strategy use. Students were found to demonstrate differential patterns of strategy use in accordance with their assigned processing conditions. Moreover, students’ use of strategies directed toward multiple texts was found to predict multiple text task performance.